Ten years after 9/11 : rethinking the jihadist threat - Acharya, Arabinda (New York : Routledge, 2013)
"Ten years after the 9/11 attacks, this book reassesses the effectiveness of the "War on Terror", considers how al-Qaeda and other jihadist movements are faring, explores the impact of wider developments in the Islamic world such as the Arab Spring, and discusses whether all this suggests that a new approach to containing international, especially jihadist, terrorism is needed"--Provided by publisher.
9/11 and globalization of violence -- Construction of the adversary -- Strategy of the global jihadist movement -- Tactics of the global jihadist movement -- Fighting the jihadist threat -- Ten years after : bringing the conflict to an end -- Conclusion : stealing jihadists' playbook, exploiting the fissures within the jihadist movement.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Qaida (Organization); Terrorism -- Prevention; Terrorism -- Religious aspects -- Islam; Jihad; War on Terrorism, 2001-2009.; Electronic books